Political Discourse before the Multiculturalism of the Spanish Right: A Comparative Analysis between PP and Vox - León-Ranero, José M.; Cheddadi El Haddad, Zakariae (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2024)
The issue of multiculturalism in a Spanish context of electoral growth of the radical right-wing party Vox has a renewed importance. This article analyses comparatively the discourses on multiculturalism of the main centre-right and radical right parties in Spain. Through content analysis applied to a new database of Twitter messages from the main PP and Vox accounts, it is concluded that while both parties use a pragmatic strategy based on utilitarian criticisms of multicultural policies, Vox, which has the discourse most opposed to multiculturalism on the Spanish right, differs from the national centre-right in that it presents a discourse with an argumentative pattern based on identity differentiation, as opposed to the purely pragmatic expression of the PP.